Chinese Nationalism And Cross-strait Relations In The Post-war Era - S. Rich, Timothy (Penerbit Universiti Sains Malaysia (USM Press), 2011)
Taiwan has played a prominent role in Chinese politics since the founding of the People's Republic of China (PRC) in 1949. For decades, the Chinese Communist Party (CCP) called for the "liberation" of the island, with the tone of the rhetoric changing but not the goal of unification. While cross-strait relations may have warmed under the Ma Ying-jeou administration and Sino-American relations beyond the Taiwan issue have greatly improved in the past decade, the role which Taiwan plays in Chinese nationalism may still lead to an undesired conflict. This article highlights the role of Taiwan within the Chinese nationalism and specifically how the island's democratisation challenges this narrative. While economic relations between both sides increase, these underlying tensions do not preclude future military confrontation.